Development of vaccines from nosocomial strains of P. aeruginosa for preventive immunization of risk groups in the conditions of war - Dercach, Svitlana; Kutsai, Nataly; Sklyar, Nadiya; Maryushchenko, Anatoly; Dyachenko, Valentina (Annals of Mechnikov’s Institute, 2024)
The problem of adequate therapy and prevention of purulent-inflammatory complications caused by nosocomial strains acquires special importance in the conditions of military operations. The structure of nosocomial infections in hospitals of different profiles is quite different, but P. aeruginosa is the most significant pathogen. To date, comprehensively studied harmless highly effective means of combating blue pus infection, including specific vaccines, have not been implemented. We consider the production of immunostimulating drugs from hospital strains (hereinafter - hospital vaccines) to be the most promising. Candidate strains should be circulating local polyresistant nosocomial strains, extracted from patients in foci of infection, in particular, with ventilator-associated pneumonia. The aim of the study. Analytical-experimental substantiation of current areas of improvement of immunoprophylaxis and vaccine therapy of pyogenic infection in the conditions of martial law. Materials and methods. Analysis of professional literary sources of information. Experimental study of vaccine samples from nosocomial strains of P. aeruginosa, obtained by the photodynamic method (5 samples), on purebred white mice (160 animals ), which were kept in the vivarium of the Institute of Medical Sciences of the National Academy of Medical Sciences under standard conditions. All experiments were performed in triplicate in accordance with international rules (Directive 86/609/EEC) and Rules for working with animals (approved by the Committee on Bioethics of the State University of IMI of the National Academy of Sciences of the Russian Academy of Sciences). The protective properties of vaccine samples were studied on laboratory animals by administering 0.2 ml subcutaneously or 0.5 ml intraperitoneally. Control infection was carried out with homologous and heterogeneous strains of P. aeruginosa with determination of LD 50 and survival rates. To study the effectiveness of vaccine therapy, a group of mice was injected with an infectious dose of P. aeruginosa culture, and the next day - a multi-strain vaccine in a dose of 0.2 ml subcutaneously, repeating the injections on the 3rd and 7th day. Non-vaccinated mice were used as a control group. The obtained research results were processed by the method of variational statistics using the MS Excel 2003 program using the x2 criterion and univariate variance analysis (р ≤ 0.05). Research results. The effectiveness of the developed vaccine samples was studied when the drug was administered parenterally to laboratory animals by subcutaneous and intraperitoneal vaccination. Experimental studies have confirmed the protective effectiveness of the obtained samples of blue pus vaccine and its possible use in immunoprophylaxis and autovaccine therapy. Indicators of protective activity of multistrain vaccine samples from nosocomial strains varied from 78.6% to 88.9%, and in the control - from 18.8% to 22.2%. The experiment studied the prospects of using autovaccines in the treatment of mice previously infected with homologous strains of P. aeruginosa. At the same time, the survival rates were 71.8%, that is, they were three times higher than in the control group. Moreover, even in the absence of complete recovery, treatment with autovaccine significantly extended their life (up to 20-30 days) and reduced the degree of clinical symptoms of the disease. The introduction of the so-called hospital vaccine prepared from several actual hospital strains of P. aeruginosa into experimental animals, even during the presence of clinical manifestations of infection (on the 3rd-7th day after infection), was also effective, since the number of dead animals was significantly lower (x2 < 0, 05). The obtained results proved that blue-pus vaccines developed in this way can be recommended for the treatment of blue-pus infection [10,15,16]. In our opinion, it is no less promising to determine the possibility of moving away from the traumatic method of immunization, replacing it with a mucosal one. This is another direction of research, which is especially relevant in wartime conditions, for victims of hostilities with the aim of preventing ventilator-associated pneumonia. Conclusion. Analytical analysis of the incidence of nosocomial infections and the problems of combating them in the conditions of martial law, as well as the results of own research, allows us to outline the directions for improving the means of immunoprophylaxis and vaccine therapy of pyelonephritis. The method of obtaining immunogens developed on the Pseudomonas aeruginosa model can be successful in the development of vaccines also from other bacteria-causing purulent-inflammatory diseases (Acinetobacter, proteus or Escherichia coli, staphylococci, etc.) and promising for the construction of combined vaccine preparations. This will contribute to increasing the effectiveness of the fight against nosocomial infections in both wartime and peaceful postwar times. Keywords: Pseudomonas aeruginosa, nosocomial strains, vaccines, war condition